The Use of Stimulant Augmentation of Second Generation Antipsychotics in the Management of Negative Symptoms of Schizophrenia: A Case Report - Azizi, Heela; Zeng, Yu Hao; Kallikkadan, Jisha; Kahn, Alexa; Olayinka, Olaniyi; Popoola, Olusegun; Khan, Tasmia; Rimawi, Dina; Malik, Ali; Williams, Shantale; et al. (International Journal of Innovative Research in Medical Science, 2018)
Background: Negative symptoms of schizophrenia have been demonstrated to be due to decreased dopamine in the mesocortical pathways. Stimulant medications are a class of medications that can increase dopamine activity in the mesocortical pathway. Case Presentation: We present the case of a patient whose negative symptoms improved from a Positive and Negative Syndrome (PANSS) score of 39 to 11 on the negative symptoms subscale during a three-week trial of dopamine agonist augmentation of antipsychotic therapy. The score on the positive symptoms subscale on PANSS remained low with a two-point reduction at the end of the three-week period. Conclusion: The potential benefits of using stimulant medications in treating negative symptoms of schizophrenia are discussed.